2019
DOI: 10.1016/j.foodchem.2018.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-scale produced fermented lentil protects against t-BHP-triggered oxidative stress by activation of Nrf2 dependent on SAPK/JNK phosphorylation

Abstract: Fermented lentil (FL) produced using L. plantarum and Savinase in alkaline conditions relieves metabolic alterations and oxidative stress in Zucker rats with metabolic syndrome. Here, we investigated the effect of up scaling the fermentation process on chemical composition and biological activity of FL. Moreover, we studied the molecular mechanisms by which FL exert a cytoprotective effect against oxidative stress in tert-butyl hydroperoxide (t-BHP)-challenged RAW264.7 macrophages. Up-scale production reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Similarly, the viability of macrophages was significantly reduced after treatment with t -BOOH (0.25 mM) by up to 44% ( Figure 2 A–D). Recent studies have also reported significant decreases (39%) of cell viability after treatment of RAW264.7 cells with 1 mM t -BOOH for 3 h [ 65 ]. Pre-treatment of Caco-2 cells with tested peptides before induction with t -BOOH for 1.5 h did not exert any protection from the effects of this chemical.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the viability of macrophages was significantly reduced after treatment with t -BOOH (0.25 mM) by up to 44% ( Figure 2 A–D). Recent studies have also reported significant decreases (39%) of cell viability after treatment of RAW264.7 cells with 1 mM t -BOOH for 3 h [ 65 ]. Pre-treatment of Caco-2 cells with tested peptides before induction with t -BOOH for 1.5 h did not exert any protection from the effects of this chemical.…”
Section: Resultsmentioning
confidence: 99%
“…As a range of bioactive compounds, such as sulforaphane, curcumin and alkyl catechols, stimulate Nrf2 they decrease chronic inflammation and improve the antioxidant responses (Alvarenga et al, 2020;Cardozo et al, 2021;De Almeida Alvarenga et al, 2019). Furthermore, the biotransformation of bioactive compounds such as oligopeptides, phenolic acids, and flavanols present in fermented food by LAB during the fermentation process potentiates antioxidant and anti-inflammatory action of such compounds by improving their bioavailability (Bautista-Expósito et al, 2019;Chiu et al, 2019;Khan et al, 2020;Senger et al, 2016;P. S. Wu et al, 2018).…”
Section: Fermented Food and Inflammation: A Role In Regulating Nrf2 A...mentioning
confidence: 99%
“…Fermented food products facilitate the dissociation of Keap1 from Nrf2 (Zhao & Shah, 2016) (increase the phosphorylation of extracellular signal-regulated kinase (ERK) (S. B. Lin et al, 2018), and facilitate Nrf2 translocation to the nucleus (Ardiansyah et al, 2015;Bautista-Expósito et al, 2019;Khan et al, 2020). Consequently, there is an increase in the expressions of Nrf2-dependent phase II enzyme genes such as heme oxygenase-1 (HO-1) (S. Kim et al, 2018;Park et al, 2020), catalase, glutathione peroxidase (GPx), superoxide dismutase (SOD), quinone oxidoreductase (NQO1) (Fuda et al, 2019).…”
Section: Some Types Of Fermented Foods Mitigate Inflammatory Processe...mentioning
confidence: 99%